Using Picture Series to Improve Speaking Ability of the Seventh Grade Students of SMP 34 Pekanbaru - Faszanaria Maya Maya; Rumiri '; Syafri K ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:The research is a classroom research that was conducted based on the problem occurred at the seventh grade students of SMP 34 Pekanbaru; namely the students were lack in speaking that influence them got poor sore in test. Therefore, this research was aimed at studying the improvement on the ability of the seventh grade students of SMP 34 Pekanbaru in speaking by using picture series. Besides, vocabulary is mostly improved after being taught by using picture series. The participants were 40 students from VII 4 of SMP 34 Pekanbaru. This research was conducted in three cycles. The data collection technique was obtained through (1) observation sheet which was applied to know the students and teacher performance during the teaching and learning process, (2) test was done to measure students’ achievement, and (3) field note was obtain information about teacher, the students activities and performance in the teaching and learning process during the implementation of picture series. The research finding can briefly explain as follow: first the student’s students speaking ability could be improved by using Picture series. Before the research was done, the average score of students was only 56,5 in pretest. After the research was done for cycle 1,it improved to 65,4. Then, In cycle 2 increased up to 70,3 and in cycle 3 up again to 76,8. Second, the observation sheet and field note result showed that the used of picture series make the teaching process more effective and it also helped students’ improve their speaking ability and more active in learning process. This improvement happened because this picture series method is appropriate to be applied to the class. Keyword: Picture Series, Students’ Speaking Ability